Marketing VAS Innovation Case of Kalkulator Nutrisi (KANU) - Saputra, Bayu Kusuma Adi; Hudrasyah, Herry (The Indonesian Journal of Business Administration, 2013)
VAS (Value Added Services) define as services which are not basic telecommunication services. VAS has become alternative for telecommunication opertor in order to gain revenue since the average revenue per user is quite low. VAS industry especially text based services immediatly experienced reflux due to several fraud such us pulse stealing, scam, and other form of business model abuse. In October 2011 Indonesia government takes action by deciding morotarium to stop all VAS services business and Telecommunication operator need to restart the services. The morotarium made VAS operator lass all the customer and they need to regain cusomer. Since that day october were known as Black October for telecommunication operator and VAS player. KANU or Kalkulator built by Creative Indonesia is one of VAS Innovation. Built to help parents in take care ot their child food and nutrition. KANU first launch based on mobile content business model and suffered from government morotarium due to fraud of VAS services. Creative Indonesia has to face two challenges. The Â first challanges come from VAS business environment and second challange was the fact that they still in introduction stage of product life cycle.Â Keywords: Value Added Services (VAS), Innovation, Consumer Perception